Efficient hydrogen evolution reaction catalyzed by molybdenum carbide and molybdenum nitride nanocatalysts synthesized via the urea glass route1. Issue 16 (28th April 2015) - Ma, Liang; Ting, Louisa Rui Lin; Molinari, Valerio; Giordano, Cristina; Yeo, Boon Siang
<x xml:space="preserve">Abstract</x> Hydrogen evolution was performed in KOH and H2SO4 electrolytes using α-Mo2C and γ-Mo2N synthesized by the 'urea glass' route. α-Mo2C shows excellent performance especially in KOH.